Improvement of MAPbI3 perovskite blend with TiO2 nanoparticles as ReRAM device - Thien G.S.H.; Talik N.A.; Yap B.K.; Nakajima H.; Tunmee S.; Chanlek N.; Goh B.T. (Elsevier Ltd, 2023)
Lead compounds; Molar ratio; Morphology; Nanoparticles; organic-inorganic materials; Perovskite; Rhenium compounds; RRAM; Titanium dioxide; Bi-layer devices; Carrier injection; Hybrid organic-inorganic; Multiple applications; Resistive Random Access Memory (ReRAM); Surface coverages; Titanium dioxides (TiO2); Two-step coatings; TiO2 nanoparticles